2021
DOI: 10.1021/acs.jafc.1c05727
|View full text |Cite
|
Sign up to set email alerts
|

Adduct Formation of Acrolein with Cyanidin-3-O-glucoside and Its Degradants/Metabolites during Thermal Processing or In Vivo after Consumption of Red Bayberry

Abstract: Acrolein (ACR) derives from the external environment and the endogenous metabolism of organisms. It has super-reactivity and can induce various diseases. We investigated the capacity of cyanidin-3-O-glucoside (C3G) and its degradants/metabolites to capture ACR during thermal processing or in vivo. Our results indicated that both C3G and its degradants, including phloroglucinaldehyde (PGA) and protocatechuic acid (PCA), could efficiently trap ACR to form adducts, such as C3G–ACR, C3G–2ACR, PGA–ACR, PGA–2ACR, PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Numerous studies have reported that natural polyphenols or flavonoids, such as phloretin, 12 epigallocatechin gallate, genistein, 13 cyanidin-3- O -glucoside, 14 cardamomin, and alpinetin, 15 can effectively scavenge ACR in vitro and in vivo , in both mice and humans. Additionally, our previous study demonstrated that curcumin in combination with quercetin synergistically inhibited ACR formation in roasted chicken wings.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have reported that natural polyphenols or flavonoids, such as phloretin, 12 epigallocatechin gallate, genistein, 13 cyanidin-3- O -glucoside, 14 cardamomin, and alpinetin, 15 can effectively scavenge ACR in vitro and in vivo , in both mice and humans. Additionally, our previous study demonstrated that curcumin in combination with quercetin synergistically inhibited ACR formation in roasted chicken wings.…”
Section: Introductionmentioning
confidence: 99%
“…After supplementation with quercetin by oral gavage, the quercetin‐MGO adduct was detected in mouse urine and feces (Zhao et al., 2021). In addition, a recent study successfully identified the acrolein adducts of C3G and its metabolites in mouse feces and human urine and feces after the consumption of red bayberry (Song, Lu, Lu et al., 2021). It is important to note that D3G, D3R, C3G, and C3R could be detected in human plasma at 90 min after ingestion of blackcurrant juice (Nielsen et al., 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty male Institute of Cancer Research (ICR) mice were fed ACR with or without C3G, and the feces contained adducts of C3G and its metabolites conjugated with ACR. C3G and its degradants, such as phloroglucinaldehyde and protocatechuic acid (PCA), could readily bind ACR to generate adducts, such as C3G‐ACR, C3G‐2ACR, PGA‐ACR, PGA‐2ACR, PCA‐ACR, and PCA‐2ACR, which could be detected in feces and urine (Song et al., 2021a). In summary, these findings imply that the protective effect of anthocyanins is unique and that it may function as an ACR inhibitor.…”
Section: Influence Of Anthocyanins On Contaminants From Food Processingmentioning
confidence: 99%